A Multiple-Dimensional Tree Routing Protocol for Multisink Wireless Sensor Networks Based on Ant Colony Optimization. (4th November 2012) - Zhou, Hui; Qing, Dongliang; Zhang, Xiaomei; Yuan, Honglin; Xu, Chen
Abstract : Routing protocol is an important topic in the wireless sensor networks. For MultiSink wireless sensor networks, the routing protocol designs and implementations are more difficult due to the structure complexity. The paper deals with the problem of a multiple-dimensional tree routing protocol for multisink wireless sensor networks based on ant colony optimization. The proposed protocol is as follows: (1) listening mechanism is used to establish and maintain multidimensional tree routing topology; (2) taking into consideration hops, packet losses, retransmission, and delay account, a distributed ant colony algorithm is proposed. When nodes select routes in the data transmission, the algorithm is utilized to realize the real-time optimization by coordination between nodes. The simulation results show that the proposed protocol can realize the QoS optimization for multisink wireless sensor networks, and its performance is better than the routing protocol of minimum hop numbers.